Different vegetal protein hydrolysates distinctively alleviate salinity stress in vegetable crops: A case study on tomato and lettuce - Zuluaga, Monica Yorlady Alzate; Monterisi, Sonia; Rouphael, Youssef; Colla, Giuseppe; Lucini, Luigi; Cesco, Stefano; Pii, Youry (Frontiers in Plant Science, 2023)
Plants have evolved diverse plant-species specific tolerance mechanisms to cope with salt stress. However, these adaptive strategies often inefficiently mitigate the stress related to increasing salinity. In this respect, plant-based biostimulants have gained increasing popularity since they can alleviate deleterious effects of salinity. Hence, this study aimed to evaluate the sensitivity of tomato and lettuce plants grown under high salinity and the possible protective effects of four biostimulants based on vegetal protein hydrolysates. Plants were set in a 2 × 5 factorial experimental design completely randomized with two salt conditions, no salt (0 mM) and high salt (120 mM for tomato or 80 mM for lettuce), and five biostimulant treatments (C: Malvaceae-derived, P: Poaceae-derived, D: Legume-derived commercial ‘Trainer®’, H: Legume-derived commercial ‘Vegamin®’, and Control: distilled water). Our results showed that both salinity and biostimulant treatments affected the biomass accumulation in the two plant species, albeit to different extents. The salinity stress induced a higher activity of antioxidant enzymes (e.g., catalase, ascorbate peroxidase, guaiacol peroxidase and superoxide dismutase) and the overaccumulation of osmolyte proline in both lettuce and tomato plants. Interestingly, salt-stressed lettuce plants showed a higher accumulation of proline as compared to tomato plants. On the other hand, the treatment with biostimulants in salt-stressed plants caused a differential induction of enzymatic activity depending on the plant and the biostimulant considered. Overall, our results suggest that tomato plants were constitutively more tolerant to salinity than lettuce plants. As a consequence, the effectiveness of biostimulants in alleviating high salt concentrations was more evident in lettuce. Among the four biostimulants tested, P and D showed to be the most promising for the amelioration of salt stress in both the plant species, thereby suggesting their possible application in the agricultural practice.